In utero methadone exposure permanently alters anatomical and functional connectivity: A preclinical evaluation - Chin, Eric M.; Kitase, Yuma; Madurai, Nethra K.; Robinson, Shenandoah; Jantzie, Lauren L. (Frontiers in Pediatrics, 2023)
The opioid epidemic is an ongoing public health crisis, and children born following prenatal opioid exposure (POE) have increased risk of long-term cognitive and behavioral sequelae. Clinical studies have identified reduced gray matter volume and abnormal white matter microstructure in children with POE but impacts on whole-brain functional brain connectivity (FC) have not been reported. To define effects of POE on whole brain FC and white matter injury in adult animals, we performed quantitative whole-brain structural and functional MRI. We used an established rat model of POE in which we have previously reported impaired executive function in adult rats analogous to persistent neurocognitive symptoms described in humans with POE. Pregnant Sprague-Dawley rat dams received continuous methadone (12 mg/kg/day) vs. saline infusion for 28 days via osmotic mini-pumps, exposing rats to pre- and postnatal opioid until weaning. At young adult age (P60), POE and saline exposed offspring underwent in vivo MRI included diffusion tensor imaging and functional MRI (fMRI). Results indicate that fractional anisotropy (FA) was decreased in adult animals with POE [n=11] compared to saline [n=9] in major white matter tracts, including the corpus callosum (p<0.001) and external capsule (p<0.01). This change in FA was concomitant with reduced axial diffusivity in the external capsule (p<0.01) and increased radial diffusivity in the corpus callosum (p<0.01). fMRI analyses reveal brainwide FC was diffusely lower in POE (p< 10-6; 10% of variance explained by group). Decreased connectivity in cortical-cortical and cortico-basal ganglia circuitry was particularly prominent with large effect sizes (Glass’s Δ >1). Taken together, these data confirm POE reduces brainwide functional connectivity as well as microstructural integrity of major white matter tracts. Altered neural circuitry, dysregulated network refinement, and diffuse network dysfunction have been implicated in executive function deficits that are common in children with POE. FC may serve as a translatable biomarker in children with POE.